PRACTICAL DESCRIPTION OF THE IMPORTANT STAGES OF PERFORMING WORKS WRITTEN FOR THE “CHOIR” UNDER THE ACCOMPANIMENT OF A CONDUCTOR AND CONDUCTING WHILE LISTENING TO THE ACCOMPANIMENT PART. - Salimov, Sherzod Shozargarovich; Normuminova, Gulmira Komiljonovna (INTERNATIONAL CONFERENCES, 2023)
The basic harmonic basis of the works written for the choir is the advanced methods of interpreting the color of the accompanying sounds in full performance, which show a strong interdependence through the melody, scale, rhythm of the piano part.